Secular variation of Earth magnetism in Plio-Pleistocene basalts of eastern Iceland (Dataset) ... - H. Wensink (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Secular variation of Earth magnetism in Plio-Pleistocene basalts of eastern Iceland ...